DIGITAL TECHNOLOGY INTEGRATION IN DIFFERENTIATED INSTRUCTION FOR ISLAMIC EDUCATION - Imam Asyrofi (Indonesian Journal of Education and Youth Development, 2025)
This study examines the role of digital technology in supporting differentiated instruction in Islamic education. Using a literature review methodology, it analyzes existing scholarly work to synthesize how digital tools such as e-learning platforms, mobile apps, and interactive resources facilitate tailored learning experiences. The findings indicate that digital technology effectively enables the differentiation of content, process, and product, thereby enhancing student engagement and learning outcomes. However, its implementation faces challenges such as the digital divide, lack of teacher readiness, and the need to balance technological innovation with Islamic values. This research concludes that digital technology is crucial for modernizing Islamic pedagogy, recommending investment in teacher training, the development of Islamic-oriented digital resources, and further research to ensure the relevance and effectiveness of Islamic education in the digital age.